Implementasi Good Corporate Governance (GCG) Pada Badan Usaha Milik Daerah (BUMD) PT. Bank Nagari Provinsi Sumatera Barat - Alika, Yulvia; Adi Putri, Indah; Rika Valentina, Tengku (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This study analyzes the implementation practices of Good Corporate Governance (GCG) principles at the Regional-Owned Enterprise (BUMD) PT Bank Nagari in West Sumatra and its implications for Regional Original Income (PAD) in 2023. This study uses a qualitative approach with a descriptive method. Primary data was obtained through in-depth interviews with key informants from PT Bank Nagari management and local government officials, while secondary data was collected from financial reports, policy documents, and official publications. Triangulation techniques were used to ensure data validity. The results of the study indicate that the implementation of GCG principles, including transparency, accountability, responsibility, independence, and fairness, has been running well at PT Bank Nagari. One of the main quantitative findings is a 25% increase in dividends in 2023 compared to the previous year, with a total contribution of IDR 113.87 billion to the PAD of West Sumatra Province. Transparency is realized through the publication of open and accurate financial reports, while accountability can be seen from the internal and external monitoring mechanisms that are carried out consistently. The implementation of GCG also encourages the company's operational efficiency and strengthens Bank Nagari's position as a major contributor to regional income. With the commitment of internal management and active supervision from the local government, GCG plays an important role in improving fiscal stability and regional economic development.